From Chagatai to German: Strategies for Rendering Babur’s Proverbs in H. Dalov’s Translation - Dilrabokhon Abdurakhmonova (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This article examines how proverbs and proverbial expressions in Zahiriddin Muhammad Babur’s Baburnama are rendered in H. Dalov’s translation (into German, with Uzbek source passages). The Baburnama is celebrated for its direct, unornamented style and its closeness to living speech, in which proverbs play a pivotal role. We outline why translating proverbs is among the most difficult tasks in translation studies, review classic approaches (e.g., A. V. Fedorov), and analyze Dalov’s concrete solutions. Using a qualitative, example-driven method, we group the book’s proverbs by theme (friendship/brotherhood, enmity and wrongdoing, practical wisdom, loyalty and trust, labor and discipline) and compare each with Dalov’s German renderings. We find that Dalov predominantly employs three strategies—functional equivalence, careful literal translation with stylistic smoothing, and adaptive reformulation—while preserving meaning and cultural color. Selected case studies (e.g., “Teng bo‘lmaguncha, to‘sh bo‘lmas”; “Die Tore einer Stadt kann man schließen, doch nie den Mund des Feindes”; “ko‘zlarini tuz tutti”; “Marg bo yoron sur ast”) show how proverbs intensify characterization, compress judgment, and anchor narrative stance. The discussion highlights best practices for proverb translation prioritizing function and discourse role, tracing intertextual Persian–Tajik sources, and using paratext where needed. We conclude that Dalov’s renderings are largely successful and that rigorous proverb analysis can both safeguard heritage and enhance cross-cultural readability.